Neoadjuvant immunotherapy with combined ipilimumab and nivolumab in patients with melanoma with primary or in transit disease. (1st September 2020) - Weber, J.; Glutsch, V.; Geissinger, E.; Haug, L.; Lock, J.F.; Schneider, F.; Kneitz, H.; Goebeler, M.; Schilling, B.; Gesierich, A.
Summary: The introduction of new therapeutic agents has revolutionized the treatment of metastatic melanoma. The approval of adjuvant anti‐programmed death‐1 monotherapy with nivolumab or pembrolizumab, and dabrafenib plus trametinib has recently set a new landmark in the treatment of stage III melanoma. Now, clinical trials have shown that immune checkpoint blockade can be performed in a neoadjuvant setting, an approach established as a standard therapeutic approach for other tumour entities such as breast cancer. Recent studies suggest that a pathological response achieved by neoadjuvant immunotherapy is associated with long‐term tumour control and that short neoadjuvant application of checkpoint inhibitors may be superior to adjuvant therapy. Most recently, neoadjuvant ipilimumab plus nivolumab in stage III melanoma was reported. With two courses of dose‐optimized ipilimumab (1 mg kg −1 ) combined with nivolumab (3 mg kg −1 ), pathological responses were observed in 77% of patients, while only 20% of patients experienced grade 3 or 4 adverse events. However, the neoadjuvant trials employing combined immune checkpoint blockade conducted so far have excluded patients with in transit metastases, a common finding in stage III melanoma. Here we report four patients with in transit metastases or an advanced primary tumour who have been treated with neoadjuvant ipilimumab plus nivolumab according to the OpACIN‐neo trial scheme (arm B). All patients achieved radiological disease control and a pathological response. None of the patients has relapsed so far. Linked Comment: Blankenstein and van Akkooi. Br J Dermatol 2020; 183 :421–422 .